Anger Dimensions and Mental Health Following a Disaster: Distribution and Implications After a Major Bushfire. Issue 1 (2nd November 2020) - Cowlishaw, Sean; Metcalf, Olivia; Varker, Tracey; Stone, Caleb; Molyneaux, Robyn; Gibbs, Lisa; Block, Karen; Harms, Louise; MacDougall, Colin; Gallagher, H. Colin; Bryant, Richard; Lawrence‐Wood, Ellie; et al.
Abstract: Anger is an important dimension of affect and a prominent feature of posttraumatic mental health, but it is commonly overlooked in postdisaster settings. We aimed to examine the distribution and implications of significant anger problems in the aftermath of a natural disaster, via analyses of Beyond Bushfires survey data from 736 residents of rural communities 5 years after the 2009 Black Saturday bushfires in Victoria, Australia. Assessments included the five‐item Dimensions of Anger Reaction (DAR‐5) scale along with measures of PTSD, depression, and significant mental illness, and indicators of life satisfaction, suicidality, hostile aggressive behavior, and violence exposure. The results indicated that approximately 10% of respondents from areas highly affected by the bushfires scored above the provisional cutoff criteria for significant anger problems on the DAR‐5, which was a more than 3‐fold increase, OR = 3.26, relative to respondents from areas of low‐to‐moderate bushfire impact. The rates were higher among women, younger participants, and those who were unemployed, and co‐occurred commonly, although not exclusively, with other postdisaster mental health problems. Anger problems were also associated with lower life satisfaction, β = −.31, an 8‐fold increase in suicidal ideation, OR = 8.68, and a nearly 13‐fold increase in hostile aggressive behavior, OR = 12.98. There were associations with anger problems and violence exposure, which were reduced when controlling for covariates, including probable PTSD. The findings provide evidence indicating that anger is a significant issue for postdisaster mental health and should be considered routinely alongside other posttraumatic mental health issues. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0135.R1_Cowlishaw_cantonese Traditional Chinese 憤怒維度與災難心理健康:大型叢林火災後的分佈及影響 摘要: 憤怒是情感的一個重要維度, 也是創傷後心理健康的一個突出特徵, 但在災後環境中通常被忽視。我們旨在通過對2009年澳大利亞維多利亞州黑色星期六叢林大火5年後736名農村社區居民的「超越叢林大火」調查數據的分析, 研究自然災害後重大憤怒問題的分佈和影響。評估包括五項憤怒反應維度(DAR‐5 )量表, 以及創傷後壓力症、抑鬱症和重大精神疾病的測量, 以及生活滿意度、自殺性、敵意攻擊性行為以及暴力暴露指標。結果表明, 在受叢林火災影響較大的地區, 約有10%來自受森林火災嚴重影響地區的受訪者在DAR‐5中得分高於嚴重憤怒問題的臨時界限標準, 相對於來自低到中等森林火災影響地區的受訪者高出3倍多, =3.26 。這一比例在女性、較年輕的參與者和失業者中更高, 而且通常(雖然不完全)與其他災後心理健康問題同時出現。憤怒問題還與較低的生活滿意度有關, β =‐.31 , 自殺意念增加了8倍, OR =8.68 , 敵對性攻擊行為增加了近13倍, OR =12.98 。與憤怒問題和暴力暴露有關, 在控制協變量(包括可能的創傷後壓力症)時, 這些關聯被減少。研究結果提供的證據表明, 憤怒是災後心理健康的一個重要問題, 應該和其他創傷後心理健康問題一起被視為常規問題。 Simplified Chinese 愤怒维度与灾难心理健康:大型丛林火灾后的分布及影响 摘要: 愤怒是情感的一个重要维度, 也是创伤后心理健康的一个突出特征, 但在灾后环境中通常被忽视。我们旨在通过对2009年澳大利亚维多利亚州黑色星期六丛林大火5年后736名农村小区居民的「超越丛林大火」调查数据的分析, 研究自然灾害后重大愤怒问题的分布和影响。评估包括五项愤怒反应维度(DAR‐5 )量表, 以及创伤后压力症、抑郁症和重大精神疾病的测量, 以及生活满意度、自杀性、敌意攻击性行为以及暴力暴露指标。结果表明, 在受丛林火灾影响较大的地区, 约有10%来自受森林火灾严重影响地区的受访者在DAR‐5中得分高于严重愤怒问题的临时界限标准, 相对于来自低到中等森林火灾影响地区的受访者高出3倍多, =3.26 。这一比例在女性、较年轻的参与者和失业者中更高, 而且通常(虽然不完全)与其他灾后心理健康问题同时出现。愤怒问题还与较低的生活满意度有关, β =‐.31 , 自杀意念增加了8倍, OR =8.68 , 敌对性攻击行为增加了近13倍, OR =12.98 。与愤怒问题和暴力暴露有关, 在控制协变量(包括可能的创伤后压力症)时, 这些关联被减少。研究结果提供的证据表明, 愤怒是灾后心理健康的一个重要问题, 应该和其他创伤后心理健康问题一起被视为常规问题。